Two new species of Styela (Tunicata: Ascidiacea) from the tropical West Atlantic Ocean - de Barros, Rodolfo Corrêa; Da Rocha, Rosana Moreira (Zootaxa, 2021)
Two new species of the genus Styela are described, with very rare characteristics in this genus: both are shallow-water and tropical, with more than two gonads in each side of the body. Styela panamensis sp. nov. is described from specimens collected in Bocas del Toro, Atlantic coast of Panama, and Styela multicarpa sp. nov. from specimens collected in Espírito Santo, Brazil and Margarita Island, Venezuela. They are probably native to the south Caribbean and S. multicarpa sp. nov. is introduced in Brazil.